Enhancing the Yield and Mass Production of Vinyl Chloride Production from Ethylene and Chloride through EDC Vapor Recovery in Direct Chlorination Process - Aryaputra, Bisma Maulana; Safitri, Anindita Novia; Razita, Dayana Khalda; Setyani, Salsabila Haura Putri; Mulfiana, Alifia Zhafirah (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Vinyl chloride (C2H3Cl) is produced using ethylene (C2H4) and chlorine (Cl) as primary raw materials. In Indonesia, the demand for raw materials to produce plastics, especially PVC, continues to grow each year. The chosen method is the direct chlorination of ethylene, resulting in the production of 1,2-dichloroethane (EDC). The process involves two conversion reactors, the CRV-100 and CRV-101. The CRV-100 reactor produces EDC vapor and some EDC compounds. However, these compounds are often not recovered and are released into the atmosphere. To increase efficiency and yield the process by recycling maximize the reactants, the EDC feedstock is replenished by recycling the top product from the CRV-100 reactor. After cooling and separation, liquid EDC is recovered and reintroduced, increasing vinyl chloride production, resulting the purity has increased from 93.93% to 97.14%, the total mass production rises from 2232.8919 kg/h to 5477.0938 kg/h before optimization, representing a 145.29% yield, reflecting a significant improvement in production efficiency. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).